Buyer Engagement and Labour Conditions in Global Supply Chains: The Bangladesh Accord and Beyond. Issue 5 (24th February 2020) - Oka, Chikako; Egels‐Zandén, Niklas; Alexander, Rachel
ABSTRACT: The Accord on Fire and Building Safety in Bangladesh ('the Accord') has received both praise and criticism concerning its implications for corporate responsibility and power. This article contributes to the debate by situating the Accord within a broader set of activities that buyers are engaged in to promote better labour conditions in their supply chains. The authors identify three approaches of buyer engagement: auditing, capacity building and advocacy. Drawing on interviews conducted with European brands and retailers, the article shows how buyers perceive the merits and challenges of these approaches, and whether and how they discharge responsibility and power through these activities. The study shows that the Accord is seen primarily as part of the auditing approach with a key feature being its use of collective leverage as a means of enforcement. While greater buyer power has not necessarily been accompanied by greater responsibility, the article highlights heterogeneity among buyers in how they take up different approaches, painting a more nuanced picture of buyer responsibility and power.